Economic crises, small farmers and forest cover in Cameroon and Indonesia - Sunderlin, William D.; Resosudarmo, I.A.P.; Ndoye, O. (Kluwer Academic Publishers, 2001)
Cameroon and Indonesia are two countries that have received much attention in the literature on tropical deforestation. Both have also experienced devastating economic crises and subsequent macroeconomic adjustment policies. Through a contrast of the two countries' experiences, this chapter explores the effect of such economic events on small farmers and their forest management practices, and the subsequent effects on tropical forest cover. In both countries, economic crises led to changes in farming systems and to a significant increase in the rate of forest clearing, yet the circumstances leading to this outcome are strikingly different. In Cameroon, a collapse of the prices of leading agroexport commodities (cocoa and coffee), withdrawal of government subsidies for these commodities, and restrictions on food imports made farmer’s clear land to produce food crops for domestic consumption. In Indonesia, a drastic depreciation of the national currency against the USD made certain agroexport commodities profitable, with the consequence that many farmers cleared land to produce these crops. There are three main lessons to be drawn from a comparison of the two countries' experiences. First, opposite forms of macroeconomic destabilization (i.e. decrease or increase of agroexport prices) can lead to the same forest cover consequences. Second, this suggests that increased rates of forest clearing have more to do with destabilization, in and of itself, rather than with the direction of change in farm commodity prices. Third, policymakers should be aware of the ways in which widely differing economic shocks and macroeconomic adjustment policies can lead to unexpected, and in some cases undesirable social and environmental consequences.